Anime sebagai Media Pembelajaran Folklor Jepang - Nesa, Fakhria; Rahayu, Rachmidian (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Using anime as a learning medium innovates Japanese language education, particularly in teaching Japanese folklore. This qualitative descriptive study assesses anime's efficacy in imparting knowledge of Japanese folklore to Japanese language learners. By examining various forms of folklore literature alongside anime featuring Japanese folklore themes, the research elucidates cultural meanings and societal aspects in Japan. For instance,